Radon-222 in groundwater and effective dose due to ingestion and inhalation in the city of Ibadan, Nigeria. (24th January 2017) - Ademola, Janet Ayobami; Oyeleke, Oyebode Akanni
Abstract: Radon concentration in groundwater collected from the eleven Local Government Areas (LGAs) of Ibadan, Nigeria, was analyzed. Annual effective doses due to ingestion and inhalation of radon from the consumption of the water were determined. The arithmetic means (AMs) of radon concentration for the 11 LGAs varied from 2.18 to 76.75 Bq l −1 with a standard deviation of 1.57 and 70.64 Bq l −1, respectively. The geometric means (GMs) varied from 1.67 to 49.47 Bq l −1 with geometric standard deviation of 2.22 and 3.04, respectively. About 58% of the 84 water samples examined had a higher concentration of radon than the 11.1 Bq l −1 recommended by United States Environmental Protection Agency (USEPA); the AMs of six LGAs and GMs of three LGAs were higher than the recommended value. However the AMs and GMs of all the LGAs with about 93% of the water sampled were lower than the 100 Bq l −1 recommended by the World Health Organization and EURATOM drinking water directive. The concentration of radon varied with the geological formation of the area. The AMs of the annual effective dose due to ingestion of radon in water ranged from 0.036 to 1.261 mSv y −1, 0.071 to 2.521 mSv y −1 and 0.042 to 1.471 mSv y −1 for adult, child and infant, respectively and the GMs in the range of 0.026 to 0.813, 0.055 to 1.625 and 0.032 to 0.948 mSv y −1, respectively. The AMs of 10 LGAs and GMs of 7 LGAs were higher than the recommended reference dose level of 0.1 mSv y −1 from the consumption of water for the duration of one year for all the three categories of people. The AMs and GMs of the annual effective dose due to inhalation of radon in drinking water ranged from 0.533 to 18.82 μ Sv y −1 and 0.411 to 12.13 μ Sv y −1, respectively, contributing less to the overall dose.